Stiffness degradation of composite laminates due to matrix cracking and induced delamination during tension-tension fatigue. (July 2019) - Pakdel, Hamed; Mohammadi, Bijan
Highlights: Fatigue stiffness degradation is predicted based on physics of damage. Matrix cracking and induced delamination are considered as the common damage modes. A damage evolution criterion is proposed with limited empirical parameters. Abstract: Degradation of mechanical properties of laminates during uniaxial tension-tension fatigue is analytically and experimentally investigated. A unit-cell based stress analysis is developed accompanied by a two-stage energy-based power law evolution rule to predict sequential propagation of matrix cracks and induced delaminations. Two power law damage evolutions are proposed to relate the rate of crack density accumulation or induced delamination propagation to the corresponding energy release rates. Analytically predicted stiffness reductions of carbon-epocy specimens are shown to be in agreement with experimental observations. The procedure is argued to be capable of predicting fatigue behavior of laminates with limited empirical parameters.